TRACHEOSTOMY IN THE PATIENT WITH DISSEMINATED INTRAVASCULAR COAGULATION - A. V. Schyogolev; D. A. Аver’yanov; E. P. Makarenko; M. V. Kuznetsov; A. A. Emel’yanov (Вестник анестезиологии и реаниматологии, 2017)
The article presents the description of successful tracheostomy in the patient suffering from severe pneumonia and disseminated intravascular coagulation. In order to prevent peri-operative hemorrhage complications one can use endoscopic dilatational technique of tracheostomy, ultrasound examination of the neck prior to the surgery, intra-operative lining of the stoma with hemostatic material.